Gopher FITStep Pro accuracy when measuring steps and moderate-to-vigorous physical activity - Brian Ali; Justin A. Haegele (Palacký University Olomouc, 2017)
Background: The Gopher FITStep Pro (GFSP) is a commercially available objective physical activity monitor that records steps taken and moderate-to-vigorous physical activity (MVPA). Objective: The purpose of this study was to evaluate the accuracy of the GFSP for measuring steps taken in a guided walking condition and MVPA during planned fitness activities. Method: University-aged participants (N = 35, Mage = 20) wore two GFSP (right and left side) pedometers and one ActiGraph GT3X+ accelerometer during both conditions. Results: Paired samples t-tests determined that self-step counts in the guided walking condition were not significantly different than the right side GFSP (p = .084) but were significantly different from the left side GFSP (p = .006). Mean absolute percent error (MAPE) was less than 3% between self-step counts with the left (1.9%) and right side GFPS (1.7%). However, MVPA estimates were significantly different between the GT3X+ accelerometer and the left side and right side GFSP (p < .001). High MAPE occurred between the GT3X+ accelerometer with the left (51%) and right side GFSP (41%) in the planned fitness activity condition. Conclusion: The GFSP may be an appropriate instrument for estimating steps, however users should be cautious when consuming MVPA estimates for educational, research, or health-related purposes.